Profil Metakognisi Siswa dalam Menyelesaikan Soal Cerita Pada Materi SPLDV Ditinjau dari Kecerdasan Interpersonal dan Intrapersonal - Hastari, Ratri Candra; Altina, Riris (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2024)
The purpose of this study is to describe the metacognitive profile of students of class X SMKN 2 Boyolangu in solving mathematical story questions on SPLDV material in interpersonal intelligence and to describe the metacognitis profile of students of class X SMKN 2 Boyolangu in solving mathematical stories on SPLDV material in the subject of intrapersonal intelligence. This research is a qualitative description study. The main instrument is the researcher himself as the main instrument in data collection, assisted by supporting instruments is as follows: 1) Mathematical story tests using metacognitive 2) Interpersonal intelligence questionnaire 3) Intrapersonal intelligence questionnaire and 4) Interview guidelines. Metacognitive profiles of subjects who have interpersonal intelligence (social intelligence). From the activities carried out by subjects who have interpersonal intelligence or intelligence from social has a type of metacognitive awareness and metacognitive regulation. Metacognition profiles of subjects that have intrapersonal intelligence (self -intelligence), from activities carried out by subjects who have intrapersonal intelligence have a type of metacognitive awareness.